2020
DOI: 10.22271/chemi.2020.v8.i6aj.11156
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of standard heterosis over environments for fruit yield and its attributes in Okra [Abelmoschus esculentus (L.) Moench]

Abstract: Heterosis breeding has proven to be a potential method of increasing yield in the crops. It enables early identification of superior/potential crosses which is necessary to handle the material in advance generations, effectively and gainfully. An experiment was conducted to evaluate 35 genotypes in four different environments at Navsari Agricultural University. The experimental material consisted of 35 genotypes; representing 24 hybrids developed in line x tester mating of 10 diverse parents and commercial hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The rainfall was relatively on higher side than normal in Months of May-June which caused increased load of insect-pests. Results corroborate the findings of Patel et al (2009) where it is reported that drip irrigation with fertigation resulted in yield increase of 46.25 percent as compared to surface irrigated crop. the first and second year.…”
Section: Yield Attributes and Fruit Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…The rainfall was relatively on higher side than normal in Months of May-June which caused increased load of insect-pests. Results corroborate the findings of Patel et al (2009) where it is reported that drip irrigation with fertigation resulted in yield increase of 46.25 percent as compared to surface irrigated crop. the first and second year.…”
Section: Yield Attributes and Fruit Yieldsupporting
confidence: 89%
“…Many researchers have reported higher application efficiency of drip irrigation over conventional irrigation methods. In study conducted at Anand, Gujrat, Patel et al (2009) reported 46.3 percent higher yield of okra with water saving of 18 percent under drip irrigation as compared to conventional furrow irrigation. Nair et al (2017) also reported that drip fertigated (100% water soluble fertilizers) crop of okra recorded 46.0 percent higher fruit yield as compared to drip irrigated crop with basal application of fertilizers.…”
Section: Angrej Singh* Sunil Garg and Kg Singhmentioning
confidence: 96%
“…Apart from this, also there are a large number of reasons owing to popularity of okra among growers' community which includes a minuscule lifecycle, photo-insensitive nature that leads to raising two crops in a year and an extensive shelf life. In spite of being a well-liked crop, productivity of okra is low across Indian domain due to several factors such as wide scale cultivation of poor performing OPVs, lack of site/environment speci c varieties/hybrids with higher resistance to pests like fruit and shoot borer and diseases like okra yellow vein mosaic virus or okra enation leaf curl virus (Patel et al 2020). Farmers are well acquainted with the importance of hybrid technology but, the problem is lack of environment/location speci c hybrids that can give stable and high yield.…”
Section: Introductionmentioning
confidence: 99%
“…With India holding the distinction of being the world's largest producer of okra, this vegetable is grown throughout the year in the country to ensure a continuous supply of tender fruits (Javed et al 2009). The immature pods were useful for making pickles (Hadiaya et al, 2018). The mucilaginous property of okra is meant for its cooking and as plasma replacer (Mir et al,2017).…”
Section: Introductionmentioning
confidence: 99%